Bending Sensors Based on Thin Films of Semitransparent Bithiophene‐Fulleropyrrolidine Bisadducts. Issue 11 (6th October 2020) - Chiappara, Clara; Campisciano, Vincenzo; Arrabito, Giuseppe; Errico, Vito; Saggio, Giovanni; Buscarino, Gianpiero; Scopelliti, Michelangelo; Gruttadauria, Michelangelo; Giacalone, Francesco; Pignataro, Bruno
Abstract: A novel bithiophene‐fulleropyrrolidine bisadducts system (bis‐Th2PC60 ) was synthesized and electropolymerized by chronoamperometry onto flexible ITO/PET substrates. The resulting semitransparent thin film was characterized by XPS, FT‐IR, cyclic voltammetry and optical techniques, confirming the good outcome of the electropolymerization process. AFM investigations permitted to highlight an inherent disordered granular morphology, in which the grain‐to‐grain separation depends upon the application of bending. The electrical resistance of the thin film was characterized as a function of bending (in the range 0°–90°), showing promising responsivity to low bending angles (10°–30°). The ΔR/R0 variations turn out to be 8 %, 16 % and 20 % for bending angles equal to 10°, 20° and 30°, respectively. This study represents a first step towards the understanding of piezoresistive properties in electropolymerized fullerenes‐based thin films, opening up applications as bending sensor. Abstract : Piezoresistive material for bending sensors : A new semitransparent bithiophene‐fulleropyrrolidine thin film was electropolymerized by chronoamperometry on flexible ITO/PET substrates. The polymeric system was characterized by FT‐IR, XPS, CV and optical techniques, showing transmittance of about 78% and excellent responsivity as bending sensor at low angles (10°–30°). At larger bending angles (40°–90°), the response was lower in accordance with piezoresistive sensing based on grains separation. This novel material opens up applications for bending sensors requiring high precision for small bending angles.